2017
DOI: 10.1371/journal.pone.0183760
|View full text |Cite
|
Sign up to set email alerts
|

Histones bundle F-actin filaments and affect actin structure

Abstract: Histones are small polycationic proteins complexed with DNA located in the cell nucleus. Upon apoptosis they are secreted from the cells and react with extracellular polyanionic compounds. Actin which is a polyanionic protein, is also secreted from necrotic cells and interacts with histones. We showed that both histone mixture (histone type III) and the recombinant H2A histone bundles F-actin, increases the viscosity of the F-actin containing solution and polymerizes G-actin. The histone-actin bundles are rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Polyvalent cations bundle actin filaments [18] because the positively charged cations eliminate the repulsion between the negatively charged actin filaments [19]. As histone H2A, the parent molecule of buforin, also bundles actin [8], and the formation of actin bundles can have pathological consequences [20], it was of interest to study the interaction between buforin III derivatives and actin. Buforin IIIB and IIIE are polyvalent cations each containing eight extra positive charges.…”
Section: Buforin III Analogs Bundle F-actin and These F-actin Bundlementioning
confidence: 99%
See 2 more Smart Citations
“…Polyvalent cations bundle actin filaments [18] because the positively charged cations eliminate the repulsion between the negatively charged actin filaments [19]. As histone H2A, the parent molecule of buforin, also bundles actin [8], and the formation of actin bundles can have pathological consequences [20], it was of interest to study the interaction between buforin III derivatives and actin. Buforin IIIB and IIIE are polyvalent cations each containing eight extra positive charges.…”
Section: Buforin III Analogs Bundle F-actin and These F-actin Bundlementioning
confidence: 99%
“…DNA and Binding of Buforin IIIB and IIIE to DNA Polyanions dissociate polycation-induced actin filament bundles as polyanions compete with negatively charged Factin for polycations. DNA, which is a highly negatively charged polyanion, was shown to unbundle histone-induced actin bundles [8]. We studied the effect of DNA on buforin III analog-induced F-actin bundles with low speed centrifugation ( Figure 6), as the buforin-DNA complex, unlike the F-actin-buforin complex, is not sedimented under this condition.…”
Section: Dissociation Of Buforin Iii-induced Actin Bundles Bymentioning
confidence: 99%
See 1 more Smart Citation
“…We showed that histone mixture H3 (histone type III) and H2A histone bundle Factin, increase the viscosity of the F-actin containing solutions and polymerize G-actin [14]. The histone mixture-actin bundles are dissociated by DNA and 300-400 mM NaCl [14]. The histone-actin bundles are highly stable.…”
Section: Introductionmentioning
confidence: 98%
“…Extracellular histones have a bad side too, they act as inflammatory agents [13], major mediators of death in sepsis [13] and have a significant role in tissue injury and inflammation [5]. We showed that histone mixture H3 (histone type III) and H2A histone bundle Factin, increase the viscosity of the F-actin containing solutions and polymerize G-actin [14]. The histone mixture-actin bundles are dissociated by DNA and 300-400 mM NaCl [14].…”
Section: Introductionmentioning
confidence: 99%